Number9dream a novel - Mitchell, David 1969- (Random House, 2001)
"In outward form, Number9Dream is a Dickensian coming -of-age journey: Young dreamer Eiji Miyake, from remote rural Japan, thrust out on his own by his sister's death and his mother's breakdown, comes to Tokyo in pursuit of the father who abandoned him. Stumbling around this strange, awesome city, he trips over and crosses - through a hidden destiny or just monstrously bad luck - a number of its secret power centers." From the bookjacket.
Keywords: Bildungsromans.; Birthfathers -- Fiction; Children of prostitutes -- Fiction; Fathers and sons -- Fiction; Young men -- Fiction; Tokyo (Japan) -- Fiction; Bildungsromans